Formation of adaptive traits sn winter wheat intraspecific hybrids (Triticum aestivum L.) - Л. А. Коломієць (Plant Varieties Studying and Protection)
The paper covers results of studying entries of winter wheat competitive strain test for adaptive traits and characteristics of new high producing, winter-hardy cultivar Kolos Myronivshchyny.